Optimization of Key Parameters in Waste Paper Recycling Process Using Response Surface Methodology - Balooch, Najibullah; Yazdan Parast, Mohammad; Asil, Yama; Hakimi, Homayoon (Journal of Natural Sciences – Kabul University, 2026)
Paper recycling plays an essential role in environmental protection, reducing the consumption of forest resources, and achieving sustainable waste management. However, the presence of various chemical compounds, particularly printing inks, poses significant challenges to the recycling process. This study aimed to investigate the effective parameters for ink removal and to optimize the recycling conditions of office paper. Accordingly, a laboratory study was designed using the Response Surface Methodology (RSM), and the influential parameters were systematically examined. The results of the analysis of variance (ANOVA) indicated that the obtained statistical model was significant and had good predictive capability. The optimal process conditions were determined to include appropriate levels of NaOH, H2O2, and Tween-80, a pH of 8- 9, and elevated temperature. Under these conditions, the average experimental recycling yield was approximately 60%, which showed good agreement with the model-predicted value of 63%. These results demonstrate that optimizing the paper recycling process can enhance efficiency, reduce chemical consumption, and improve environmental compatibility.